Conjugated microporous polymer nanoparticles with enhanced dispersibility and water compatibility for photocatalytic applications1. Issue 31 (21st August 2015) - Ma, Beatriz Chiyin; Ghasimi, Saman; Landfester, Katharina; Vilela, Filipe; Zhang, Kai A. I.
<x xml:space="preserve">Abstract</x> Conjugated microporous polymer nanoparticles as highly dispersible heterogeneous organic photocatalysts for photocatalytic applications.